Media, Erotics, and Transnational Asia (Duke University Press, 2013)
Drawing on methods and approaches from anthropology, media studies, film theory, and cultural studies, the contributors to Media, Erotics, and Transnational Asia examine how mediated eroticism and sexuality circulating across Asia and Asian diasporas both reflect and shape the social practices of their producers and consumers. The essays in this volume cover a wide geographic and thematic range, and combine rigorous textual analysis with empirical research into the production, circulation, and consumption of various forms of media.Judith Farquhar examines how health magazines serve as sources of both medical information and erotic titillation to readers in urban China. Tom Boellstorff analyzes how queer zines produced in Indonesia construct the relationship between same-sex desire and citizenship. Purnima Mankekar examines the rearticulation of commodity affect, erotics, and nation on Indian television. Louisa Schein describes how portrayals of Hmong women in videos shot in Laos create desires for the homeland among viewers in the diaspora. Taken together, the essays offer fresh insights into research on gender, erotics, media, and Asia transnationally conceived.Contributors. Anne Allison, Tom Boellstorff, Nicole Constable, Heather Dell, Judith Farquhar, Sarah L. Friedman, Martin F. Manalansan IV, Purnima Mankekar, Louisa Schein, Everett Yuehong Zhang